The Effect of a Period of Selected Physical Activity on Improving Gross Motor Skills in Children with Developmental Coordination Disorder (DCD) - Somayeh Jokar Tang Karami; Mahmood Sheikh; Fazlollah Bagherzadeh (University of Tehran, 2018)
Developmental coordination disorder (DCD) is a motor disorder which involves gross and fine motor skills and coordination. The aim of this study was to investigate the effect of a period of selected physical activity on improving gross motor skills in female children with developmental coordination disorder (DCD). In this semi-experimental study, the sample consisted of 30 students with DCD who were selected from 400 female children in second grade of elementary school in Shiraz city by a researcher-made questionnaire and the Movement Assessment Battery for Children (MABC). The subjects were divided randomly into control (n=15) and experimental (n=15) groups after the pretest using Ulrich test for gross motor skills version 2000 (TGMD2). The experimental group performed the selected motor program for 12 sessions (3 days a week, 45 minutes per day) while the control group had their normal daily activities. Then, a posttest was held for both groups. The analysis of variance 2´2 was used for data analysis (P≤0.05). The results showed that selected physical activity had a significant effect on improving gross motor skills in children with DCD (P=0.001). Therefore, it is suggested that selected physical activities should be available for teachers and should be performed in physical education courses at schools in order to improve gross motor skills and consequently improve developmental coordination disorder in children